The role of psychodynamics in linguistics : applying the tradition of Melanie Klein to the analysis of conversational interaction - Hoyle, R (1989)
Linguistics has developed elaborate accounts of the social aspects of language use - 'how to do things with words' - but the emotional-dynamic aspects have hitherto received less attention. Such discussions of emotive or affective meaning as there have been have tended to concentrate on the linguistic resources that are coded into the language system, rather than the dynamics of emotional interaction enacted through language use. The clinical discipline of Kleinian psychoanalysis, by contrast, has made emotional dynamics its central concern. Furthermore the main tool of the psychoanalyst's trade is the verbal interpretation of the patient's material, much of which is itself verbal. These factors have led to the development in Kleinian psychodynamic theory of a particularly rich vocabulary for understanding emotional-dynamic interaction, and specifically those aspects which are verbally enacted. The goal of this thesis is to outline a linguistic theory of emotional dynamics based on insights derived from Kleinian psychoanalysis. It aims to extrapolate from a clinical context Kleinian ideas that can be integrated with those of the school of Linguistic thought that has emphasised the dynamic aspects of locally-managed discourse meaning.